Configuration mixing upon reorganization of dihedral angle induces rapid intersystem crossing in organic photoredox catalyst. Issue 23 (5th June 2020) - Kim, Hwon; Scholes, Gregory D.
Abstract : A long excited state lifetime is a desirable quality of photocatalysts because it enables a higher probability of energy or electron transfer from the photocatalyst to a substrate. Abstract : A long excited state lifetime is a desirable quality of photocatalysts because it enables a higher probability of energy or electron transfer from the photocatalyst to a substrate. However, achieving a long lifetime in organic (metal-free) catalysts is challenged by competing rapid nonradiative relaxation from excited states and relatively slow intersystem crossing into long-lived states with different spin multiplicity. In this work, we propose an intersystem crossing mechanism in heavy-metal free photocatalyst that results from reorganization of a dihedral angle between moieties. The relaxation of orthogonality of the dihedral angle and increasing the orbital overlap between the two components of the molecule changes the coupling between the configurations of singlet and triplet states, which in turn results in larger spin orbit coupling between the two manifolds as the molecule twists. We predict that this enables intersystem crossing to outcompete the singlet state lifetime.